Production Of Isoamyl Acetate With Candida Antarctica Lipase B (CALB) As Enzyme In A Solvent-Free System Using Miniaturised Intensified Reactor - Sangaran, Sathiswaran (Universiti Sains Malaysia, 2018)
Isoamyl acetate is a type of ester that has similar fragrance to banana. It is widely being used as banana flavouring in food industries. Initially, isoamyl acetate was extracted using tradition method from plants and fruits, and then followed by chemical synthesis. Over the time, the esterification process is conducted using enzyme because consumers highly prefer naturally synthesized ester compared to chemically synthesized ester. On the other hand, lately process intensification is gaining momentum among the researchers. This is because the maximum conversion and yield can be achieved in shorter time in miniaturised intensified reactors compared to the large conventional reactors. Thus this study is conducted to investigate the performance of isoamyl acetate production using enzyme Candida antarctica Lipase B (CALB) in miniaturised intensified reactors. The effect of operating parameters such as reaction temperatures, acid-alcohol ratio and presence of enzyme on the final concentration and conversion of isoamyl acetate produced was studied using One-Factor-At-A-Time (OFAT) method and also Response Surface Methodology (RSM) to optimise the results. The results of OFAT show that it is more reliable than RSM method because the regression coefficient value is very closer to unity which is more than 0.91. The optimum operating condition obtained through OFAT is 50⁰C for temperature and 0.6 for acid-alcohol ratio. The optimum temperature with enzyme is 40⁰C.